Technologies for Producing Capsules “Yuyuzin” - Zilola Vakhobdjonovna Turdieva1, Manzura Tokhirovna Mullajonova2, Umarkhon Mukhtorovich Azizov3, Dil (Indian Journal of Forensic Medicine & Toxicology, 2020)
Hypertension is a disease whose main symptom is an increase in blood pressure due to neuro-functionaldisorders of vascular tone. Hypertension affects men and women equally. The disease usually begins afterthe age of 40. This is a very common pathology. It is called the disease of the fall of life, although in recentdecades hypertension has become much younger.Capsule,substance, extract, calcium Hypertension is one of the causes of disability and mortality in patientswith disorders of the cardiovascular system.One of the causes of hypertension is prolonged and frequent neuropsychological stress, prolonged stress.Hypertension very often occurs in people whose work is associated with constant emotional stress. Peoplewho have suffered a concussion often suffer from it.The paper presents the results of the development of the optimal composition and hard gelatin capsules basedon the dry extract of Jujube fruit - Ziziphusjujuba (jujube, jilanjija). The formulation and technology of thesingle - source pharmaceutical product in the form of capsules “Yuyuzin” with antihypotensive activity wasdeveloped. As excipients used MCC, Aerosil, calcium stearate.